2021
DOI: 10.1108/oir-09-2020-0419
|View full text |Cite
|
Sign up to set email alerts
|

Arab women feelings while seeking information during COVID-19 pandemic: applying PMT constructs

Abstract: PurposeThis study investigates the effect of protection motivation theory (PMT) constructs on Arab women's feelings while seeking information during the COVID-19 pandemic.Design/methodology/approachThe study has adopted a mixed-method approach using semi-structured interviews and a questionnaire to explore PMT constructs' impact on women's feelings while seeking information on COVID-19. Several tests, such as standard deviation, mean, skewness, kurtosis and persons, were used to check the reliability of data a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 84 publications
(105 reference statements)
1
4
0
Order By: Relevance
“…Their information needs shifted towards following updates on the epidemiological situation. Previous literature supported these results and showed changes in information needs during public health emergences (Alwreikat, Shehata, & Eldakkar, 2021) and (Sharifirad et al, 2014).…”
Section: Information Needssupporting
confidence: 61%
See 1 more Smart Citation
“…Their information needs shifted towards following updates on the epidemiological situation. Previous literature supported these results and showed changes in information needs during public health emergences (Alwreikat, Shehata, & Eldakkar, 2021) and (Sharifirad et al, 2014).…”
Section: Information Needssupporting
confidence: 61%
“…Measures of stress and coping can explain such behaviour. in a very interesting study by Alwreikat, Shehata, & Eldakkar (2021) they found that Arab women had stressful times dealing with the information on COVID-19 because negative feelings as part of the threat appraisal were presence while seeking information on the virus. Such negative feelings triggers a coping behaviour to deal with information on the virus and avoid reading negative information.…”
Section: Uncertaintymentioning
confidence: 99%
“…In sum, the COVID-19-related misinformation, disinformation and conspiracy theories have arguably reached a peak amidst the pandemic, and the WHO director-general has argued that we are not just facing a pandemic; we're also fighting an infodemic. An infodemic refers to the state of over-abundance of information, including both authentic and misinformation, which prevents individuals from rationally and clearly distinguishing between verified and unverified information (Alwreikat et al, 2021;Zeng and Chan, 2021). The utilization of social media for news gathering, one's network of discussion, as well as whether an individual is literate enough to process media information, might have both contributed to and been affected by the infodemic (Apuke and Omar, 2021a).…”
Section: Problem Statementmentioning
confidence: 99%
“…In sum, the COVID-19-related misinformation, disinformation and conspiracy theories have arguably reached a peak amidst the pandemic, and the WHO director-general has argued that we are not just facing a pandemic; we're also fighting an infodemic. An infodemic refers to the state of over-abundance of information, including both authentic and misinformation, which prevents individuals from rationally and clearly distinguishing between verified and unverified information (Alwreikat et al. , 2021; Zeng and Chan, 2021).…”
Section: Problem Statementmentioning
confidence: 99%
“…In addition, it was found that exposure to misinformation increased the level of depression [69]. In order to alleviate these feelings, individuals looked for more information that might comfort them [70].…”
Section: Covid-19 Anxietymentioning
confidence: 99%